The Musical Artistry of Bheki Mseleku - Lilley, Andrew (Book collections on Project MUSE., 2020)
Bheki Mseleku is widely considered one of the most accomplished jazz musicians to have emerged from South Africa. His music has a profound significance in recalling and giving emphasis to that aspect of the African American jazz tradition originating in the rhythms and melodies of Africa. The influences of Zulu traditional music, South African township, classical music and American jazz are clearly evident and combine to create an exquisite and particularly lyrical style, evoking a sense of purity and peace that embraces the spiritual healing quality central to his musical inspiration. The Artistry of Bheki Mseleku is an in-depth study of his musical style and includes annotated transcriptions and analysis of a selection of compositions and improvisations from his most acclaimed albums including 'Celebration', 'Timelessness', 'Star Seeding', 'Beauty of Sunrise' and 'Home at Last'. Mseleku recorded with several American jazz greats including Ravi Coltrane, Joe Henderson, Pharoah Sanders, Charlie Haden, Billy Higgins and Abbey Lincoln. His music serves as a vital link to the African-American musical art form that inspired many of the South African jazz legends.